2007
DOI: 10.1071/ah070083
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting emergency department presentations

Abstract: Objective: To forecast the number of patients who will present each month at the emergency department of a hospital in regional Victoria. Methods:The data on which the forecasts are based are the number of presentations in the emergency department for each month from 2000 to 2005. The statistical forecasting methods used are exponential smoothing and Box-Jenkins methods as implemented in the software package SPSS version 14.0 (SPSS Inc, Chicago, Ill, USA). Results:For the particular time series, of the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 6 publications
0
69
0
1
Order By: Relevance
“…This is also important because new models of emergency crowding have been developed using a mathematical model of the incoming flow (patient visits). 7 Numerous authors have already become interested in the prediction of patient visits in EDs, [8][9][10][11][12][13][14][15] as well as in walk-in clinics, 6,[16][17][18] mainly using calendar variables in multiple linear regression models. 19 These methods examine correlations between patient visits and a number of independent determinants, mostly calendar variables.…”
mentioning
confidence: 99%
“…This is also important because new models of emergency crowding have been developed using a mathematical model of the incoming flow (patient visits). 7 Numerous authors have already become interested in the prediction of patient visits in EDs, [8][9][10][11][12][13][14][15] as well as in walk-in clinics, 6,[16][17][18] mainly using calendar variables in multiple linear regression models. 19 These methods examine correlations between patient visits and a number of independent determinants, mostly calendar variables.…”
mentioning
confidence: 99%
“…They discussed about strength and weakness of each method. [12] The results presented in the literature show that ARMA model [15], [16] and its variants [17] provides an analytical tool of time series very accessible both in terms of methodological constraints and the level of mathematical models used, which are less complex linear stochastic equations. In this study, ARMA model was used to describe the variation in demand for emergency care in an ED system.…”
Section: A Time Series Analysismentioning
confidence: 99%
“…They used linear regression and found that calendar features are more useful than weather features. Champion et al [5] propose using ARMIA models to forecast monthly ED presentations. Jones et al [6] investigated techniques, such as linear regression, SARIMA, exponential smoothing, time series regression and artificial neural network to forecast daily ED presentations.…”
Section: Related Workmentioning
confidence: 99%